Effects of different injection strategies on ignition and combustion characteristics in an optical PPC engine. (15th July 2020) - Zhang, Miao; Derafshzan, Saeed; Richter, Mattias; Lundgren, Marcus
Abstract: Although multiple injection strategies have a significant influence on partially premixed combustion (PPC) efficiency, the mechanisms behind the influence are still to be explained and evaluated. In this paper, single, double, and triple injection strategies are used in a heavy-duty optical engine. The effects on engine efficiency are analyzed by an energy balance method. Furthermore, the change of ignition location and combustion process under different injection cases are explored by natural luminescence recorded by a high-speed camera. The results show that, with double injections, the interaction between the main and pilot jets advances the combustion phasing nearly to the top dead center (TDC), resulting in higher efficiency. This interaction also shifts the combustion process into the piston bowl, where it has high potential to reduce heat-transfer loss. With triple injections, the interaction between the main combustion (formed by the pilot and main injections) and the post injection jet significantly affects the combustion losses. In all, the jet-jet interaction and combustion-jet interactions play a significant role in engine efficiency when using multiple injections. Highlights: Fuel stratification affects the low temperature combustion process and gross indicated efficiency. Multiple injection strategies were therefore used to study the effect on gross indicated efficiency. The strategies were studied using a combination of optical and thermodynamic tools. It was found that the fuel distribution affects both heat transfer and combustion losses. This knowledge is useful for further improving low temperature combustion concepts.